Bronchopulmonary Dysplasia in Preterm Infants Born at Less Than 32 Weeks Gestation - Yan-Ping Xu PhD (SAGE Publishing, 2016)
Objectives: Bronchopulmonary dysplasia (BPD) is a chronic pulmonary disorder affecting preterm infants. We studied the factors and echocardiographic evidence of early pulmonary hypertension (PH) associated with moderate or severe BPD. Methods: We retrospectively reviewed preterm infants who were born at <32 weeks gestation and admitted to the neonatal intensive care unit at the Children's Hospital of Zhejiang University School of Medicine between July 2013 and July 2015. Results: Forty-two preterm infants were enrolled in the study. All the patients received oxygen treatment for a mean of 62.5 ± 28.0 days. The grades of BPD were classified as follows: severe, 35.7%; moderate, 40.5%; and mild, 23.8%. The time of ventilator and oxygen supplementation was longer in infants who developed PH. Severe BPD was related to PH at 28 days. Conclusions: These findings support the notion that early pulmonary vascular disease and long-term infection in preterm infants contributes to increased susceptibility for severe BPD.